Prioritizing Type of Industry through Health Risk Assessment of Occupational Exposure to Dimethylformamide in the Workplace - Lee, Junghyun (Int J Environ Res Public Health, 2018)
The purpose of this study was to classify hazards at an industrial level and evaluate the exposure risks of workers exposed to dimethylformamide (DMF) used as a solvent in the workplace and to determine industries that need priority measures in managing DMF exposure. We calculated hazard quotients at an industrial level. The exposure data of DMF in the workplace were obtained from the work environment monitoring program provided by the Korea Occupational Safety and Health Agency. The evaluation was conducted on textile manufacturing, leather manufacturing, chemical manufacturing, pharmaceutical manufacturing, and rubber manufacturing industries, which have many unit work sites handling DMF. The highest central tendency exposure and reasonable maximum exposure were 2.13 and 18.66 mg/m(3) for the rubber product manufacturing industry, respectively. A total of 63.8% of workplaces in the textile manufacturing sector had a hazard quotient higher than 1. The highest risk for exposure to DMF is in the rubber and plastic manufacturing industry, and the lowest risk was in the medical materials and pharmaceutical manufacturing sector. Based on this study, effective management of DMF exposure could be achieved by establishing priority management measures for the textile and rubber and plastic product industries.